The geography of French agricultural co-operatives: An explanatory spatial data analysis - Chantelot Sébastien; Filippi Maryline; Peres-Quesada Stéphanie (European Regional Science Association (ERSA), 2010)
Agricultural cooperatives represent nearly 75% of all farmers in France. They have become major actors in the development of rural spaces. Over the past 30 years, French cooperatives have steadily modified their organizational structures in response to changes in the economic environment, following a major trend in the whole world (Cook and Chaddad, 2004). Whereas most cooperatives started out as simple collectors of agricultural raw materials, they have moved progressively into the agro-transformation business and became corporate groups shaped by a head group and subsidiaries such as other cooperatives or commercial companies (Filippi, Frey and Torre, 2009). These different entities structure the French agricultural cooperative system. Hence, subsidiarization opportunities particularly soften the French specific law that strictly restrains cooperative's actions within a defined territorial circumscription. As a consequence, cooperatives develop organizational structures that are increasingly distended in spatial terms (Filippi, Frey and Triboulet, 2007). That's why this paper analyses the agglomeration patterns for agricultural cooperative system in France in 2005. We adopt a methodology allowing the measurement of its degree of spatial agglomeration and the identification of its location patterns (Guillain and Le Gallo, 2008). First, we compute the locational Gini coefficient and Moran's I statistics of global spatial autocorrelation. We show that these measures provide different but complementary information about the spatial agglomeration of components of the French cooperative system. Second, we use the tools of Exploratory Spatial Data Analysis. Moran scatterplots and LISA statistics (Anselin, 1995) allow us to shed light on the uneven geographic distribution of the cooperative system across France and to identify several clusters of agricultural cooperatives. This article constitutes a first attempt in analyzing French agricultural cooperative system by using spatial data.
Keywords: C21; O18; Q13; R11; R12; 330; Agricultural cooperatives; French cooperative system; clusters; explanatory spatial data analysis; spatial autocorrelation